Effect of Palmitic Acid on Exosome-Mediated Secretion and Invasive Motility in Prostate Cancer Cells - Maly, Ivan V. (Molecules, 2020)
High fat consumption can enhance metastasis and decrease survival in prostate cancer, but the picture remains incomplete on the epidemiological and cell-biological level, impeding progress toward individualized recommendations in the clinic. Recent work has highlighted the role of exosomes secreted by prostate cancer cells in the progression of the disease, particularly in metastatic invasion, and also the utility of targeting these extracellular vesicles for diagnostics, as carriers of disease progression markers. Here, we investigated the question of a potential impact of the chief nutritional saturated fatty acid on the exosome secretion. Palmitic acid decreased the secretion of exosomes in human prostate cancer cells in vitro in a concentration-dependent manner. At the same time, the content of some prospective metastatic markers in the secreted exosomal fraction was also reduced, as was the ability of the cells to invade across extracellular matrix barriers. While by themselves our in vitro results imply that on the cell level, palmitic acid may be beneficial vis-à-vis the course of the disease, they also suggest that, by virtue of the decreased biomarker secretion, palmitic acid has the potential to cause unjustified deprioritization of treatment in obese and lipidemic men.